The relation analysis on throwing angle and motion in javelin throw - Tazuke, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction Throwing angle is important for better performance in track & field javelin throw. Javelin throwers tend to throw higher than optimal angle. Coach instructs athlete to throw lower, and thrower tries to throw the javelin lower. However, it is difficult for throwers to throw the javelin in lower angle. In this study the factors of the throwing angle in javelin throw were examined from the viewpoint of the throwing motions. Methods Subjects were 9 javelin throwers (aged 19.33 years+-1.414, best performance 55.75m+-8.047, career of javelin throw 48.22month+-1.563, body height 171.04cm+-8.042, body weight 68.39kg+-10.925), 2 female and 7 male throwers. The experiment was carried out from the throwing gate, which enables measuring the throwing angle, initial velocity and attack angle immediately, right after throwing. Subjects got their throwing angle after throwing from this gate. For the first throw, they threw the javelin normally. From the second to sixth throw, they were to declare their target throwing-angle beforehand, e.g. "higher" or "lower", those were recorded. Every throwing motion was filmed with two high-speed video cameras, film rate 250 / sec. by NAC. 21 out of 54 feasible throwing motions were analyzed by the three-dimensional analysis with motion analysis software, Dynas-3D by Shin-Osaka Shokai Co., Ltd. The correlation of the analyzed data, initial velocity of javelin (IVJ), velocity of body gravity (VBG), throwing angle (THA), attack angle (ATA), trunk angle (TRA), arm angle (ARA), arm-trunk angle (A-TA) and elbow angle (EA) etc. at release (R); last (LFC), second (SFC) and third foot contact (TFC) before releasing; third foot takeoff (TFT) before releasing were analyzed with the statistic software, SPSS. Results and Discussion A clear interactive relation was observed throwing angle and IVJ (r=-0.787, p=.01), VBG at R (r=-0.666, p=.01), THA on the XZ plane at TFT (r=-0.711, p=.01) and at TFC (r=-0.882, p=.01), TRA on the XY plane at TFC (r=0.642, p=.05), TRA on the XZ plane at R (r=0.593, p=.05) and SFC (r=0.700, p=.01), ARA on the XY plane at R (r=0.585, p=.05), and ARA on the XZ plane at SFC (r=0.552, p=.05), at TFT (r=0.803, p=.01) and at TFC (r=0.724, p=.01), and left ARA on the XY plane at R (-0.597, p=.05), at LFC (r=-0.787, p=.01) and at SFC (r=0.795, p=.01), left ARA on the XZ plane at RFC (r=0.550, p=.05) and at TFT (r=0.623, p=.05), A-TA at LFC (r=0.754, p=.01), TRA on the ZY plane at R (r=0.700, p=.01) and at TFT (r=0.561, p=.05). 3 followings were mainly suggested from the experiment. 1) When the direction of javelin leans toward X axis at TFC, the throwing angle is lower. 2) When the trunk leans toward horizontal line at TFC, the throwing angle is higher. 3) When the throwing arm leans toward horizontal line at R, the throwing angle is higher.